ANALISIS POTENSI SUMBER DAYA BATUGAMPING DI KAWASAN KARST DESA SAMANGKI, KABUPATEN MAROS, SULAWESI SELATAN - Minarti, Minarti; Jumardin, Jumardin; Munim, Abdul; Ismullah Massinai, Muhammad Fawzy; Wijaya, Arif (JFT: Jurnal Fisika dan Terapannya, 2021)
Research has been carried out in Samangki Village which aims to analyze the potential of limestone resources using the Geoelectrical Resistivity Method with the Wenner-Schlumberger configuration. Data were collected at 801904.40-802051.05 NE and 9440758.03-9440548.93 SW for 3 lines along 120 m with 10 m electrode space in a track. Acquired data were processed using Microsoft Excel, Notepad, RES2DINV, ArcGIS, and Google Earth applications to produce resistivity cross-sections and other supporting maps. Based on data interpretation, it shows that the low resistivity zone is an alluvium deposit (Qac) with resistivity value of 17.58 to 170 Ωm; and the high resistivity zone indicates the presence of limestone which is part of the Tonasa Formation (Temt). The presence of limestone on line-1 with resistivity value of 326.00 to 931.90 Ωm at position(x) 60 to 90 m, in depth(y) 1.25 to 9.26 m as shallow area, and at position 40-45 m in depth 16 to 19.8 m as the deepest area. Then the limestone on line-2 is indicated as a subsurface karst tower with a resistivity value of 462.00 to 809.36 Ωm at position 30 to 50 m in depth 1.25 to 19.8 m. Limestone also located on the northeastern edge of line-3 with resistivity values of 431.00 to 739.66 Ωm at a position of 12.5 to 17.5 m in depth of 1.25 to 6.38 m. It proves that Samangki Village has large potential for limestone resources. This research need further geoelectrical study with broad coverage area and geochemical analysis for detail karst characterization